Metallic glass based composites with precise tunable thermal expansion. (December 2022) - Sun, Fei; Lin, Hongji; Fu, Jianan; Li, Zhen; Luo, Feng; Wang, Bei; Ruan, Wenqing; Ren, Shuai; Zhang, Zhenxuan; Liang, Xiong; Ma, Jiang; Shen, Jun
Highlights: The preparation of dense and homogeneous metallic glass matrix composites was achieved. The interfacial bonding mechanism between metallic glass and additives in composites was investigated. The continuous regulation of the thermal expansion properties of composites from huge positive expansion to negative expansion was achieved. The preparation of composite materials with near-zero expansion characteristics over a wide temperature range was achieved. Abstract: Thermal expansion properties of materials are of fundamental interest and regulation of thermal expansion is significant for practical applications, but remains a challenge. We developed a moderate and efficient route for the preparation of metallic glass matrix composites, enabling precise tuning of thermal expansion properties over a wide range. Admixtures with dissimilar thermal expansion properties were successfully bonded to metallic glasses because of the unique thermoplasticity. The prepared composites achieve continuous regulation of the coefficient of thermal expansion over a broad range (9.6 ppm/K to 34 ppm/K), and high precision (0.065 ppm/K corresponds to one percent of the volume) can be realized. In addition, composites with nearly zero thermal expansion properties (average 0.19 ppm/K) in the wide temperature region (223 K to 473 K) were successfully prepared. Our approach provides a flexible and moderate pathway to achieve precise customization thermal expansion properties, promising a shift from laborious searching to precise tailoring of materials. Graphical abstract: Image, graphical abstract